Locating and Designing Journeys Home: A Literature Review - Johnson, G; Scutella, R (My University, 2012)
In this paper we review previous longitudinal research on homelessness with the aim of identifying the necessary design features of Journeys Home to enable researchers and policy makers to fill the gaps in our knowledge of the causes and consequences of homelessness. We show that despite substantial progress in homelessness research in some areas, particularly in the areas of definition and enumeration, there remains a need for large scale longitudinal data to better understand pathways into and out of homelessness. This requires a survey that is representative of a broader population of people experiencing homelessness as well as people vulnerable to homelessness. A large sample of this sort will enable researchers to rigorously examine pathways into and out of homelessness, the structural and individual level causes of homelessness, and key outcomes of homelessness.
Keywords: Life Events -- Impact; Surveys and Survey Methodology; Housing; Surveys and Survey Methodology; Disadvantage, adversity and resilience; Housing, communities and neighbourhoods; Housing; Surveys and Survey Methodology; Life Events; Impact; Adversity and resilience; Dsiadvantage, adversity and resilience; Housing